OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM UNDER ISO 45001 FOR THE REDUCTION OF OCCUPATIONAL ACCIDENTS IN THE COMPANY PROSEL INGENIERÍA S.A.C. - ALARCON-VENTURA, KATICSA (2024)
THE OBJECTIVE OF THIS RESEARCH IS TO DEMONSTRATE, THROUGH THE IMPLEMENTATION OF AN OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM BASED ON THE ISO 45001:2018 STANDARD, THE REDUCTION OF OCCUPATIONAL ACCIDENTS IN THE COMPANY PROSEL INGENIERÍA SAC. THIS IS BECAUSE, IN THIS ORGANIZATION, WHICH PROVIDES ELECTRICAL AND CIVIL SERVICES ON BOTH PUBLIC AND PRIVATE ROADS; A HIGH ACCIDENT RATE HAS BEEN EVIDENT DURING THEIR WORK DAYS. THEREFORE, THE APPLIED EXPERIMENTAL METHODOLOGY HAS BEEN USED, THROUGH THE USE OF DESCRIPTIVE AND INFERENTIAL STATISTICS FOR THE INTERPRETATION OF DATA AND VALIDATION OF THE GENERAL AND SPECIFIC HYPOTHESIS. LIKEWISE, AFTER PERFORMING THE SHAPIRO WILK TEST, TO ANALYZE THE DATA OBTAINED FROM THE 16 ACCIDENT RECORDS, WHOSE SIGNIFICANCE VALUE WAS LESS THAN 0.05, THE WILCOXON TEST WAS USED TO DETERMINE THE VALIDITY OF OUR HYPOTHESES, OBTAINING SIGNIFICANCE VALUES. LESS THAN ITS PARAMETER 0.05, CONCLUDING THE VALIDITY OF THE INITIALLY PROPOSED HYPOTHESIS. THIS IS HOW, AFTER CARRYING OUT A BASELINE DIAGNOSIS AND COMPARING IT WITH THE IMPLEMENTATION OF THE ISO 45001:2018 STANDARD, AN AVERAGE DECREASE OF 90.64% IN THE ACCIDENT FREQUENCY RATE AND A 73.85% DECREASE IN THE ACCIDENT SEVERITY INDEX WAS OBTAINED. WORK ACCIDENTS. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.